The Use of Digital Skills for Nakhon Ratchasima Buddhist College Administrations: - Pimprasan, Supot; Bunman, Narongchai; Putthaariyavong, Amonrat; Kimsua, Chonlawat; Tiamkum, Saksit (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: These days, it's thought that having digital abilities is a must for administrators, especially those in the field of education, where the chief administrator's knowledge and proficiency in digital expertise are crucial. to effectively manage education administration to accomplish the goals of the organization. The present study set out to investigate three key areas: 1) the use of digital skills by Nakhon Ratchasima Buddhist College Administrations; 2) the administrations' satisfaction with these skills; and 3) the key elements of these skills for Nakhon Ratchasima Buddhist College Administrations in Mueang District, Nakhon Ratchasima Province. Methodology: Cluster random selection was used to select a sample of 100 stakeholders, comprising 72 students, 12 staff members, and 15 teachers from Nakhon Ratchasima Buddhist College in Mueang District, Nakhon Ratchasima Province. The study was conducted during the second semester of the academic year 2023. The mean and standard deviation (S.D.) were utilized for data analysis in this study, which used a questionnaire as its instrument. Results: The Nakhon Ratchasima Buddhist College administration has made excellent use of the potential of digital skills. In addition, it was found that; (1) The study's summary of the use of digital skills by Nakhon Ratchasima Buddhist college administrators revealed a considerably high level of usage. At the highest level, the satisfaction survey regarding the utilization of digital skills for the administrations of Buddhist colleges in Nakhon Ratchasima was noteworthy. And (3) The use of digital abilities for technological communication in the administrative development of Nakhon Ratchasima Buddhist College was the most important requirement. Conclusion: The potential index showed that the demand evaluation of digital skills was employed in administrative development with digital technologies, and the usage of digital skills by the administrations of Nakhon Ratchasima Buddhist College was significantly at a high level.